One-year Retrospective Analysis of Major Oral and Maxillofacial Surgical Procedures Performed under General Anesthesia in a Tertiary Care Hospital, Rajshahi, Bangladesh (Update Dental College Journal, 2026)
Background: Major oral and maxillofacial surgeries include one large variety of procedures to include traumatic, neoplastic, cystic, and developmental pathologies. Evaluating surgical trends gives essential insights into disease burden, departmental workload and regional needs for specialized care.Objective: To analyze the spectrum, frequency and distribution of major oral and maxillofacial surgeries under general anesthesia in a tertiary care hospital over a 1-year period of time.Materials & Methods: This study was a retrospective study that was conducted in the Department of Oral and Maxillofacial Surgery, Rajshahi Medical College Hospital, Bangladesh. Records of all in-patients undergoing major maxillofacial surgical procedures under general anesthesia in the period from January-December 2024 were reviewed. Data were extracted from the operation theatre register and patient case file and were categorized according to the type of surgical procedure and analyzed descriptively.Results: A total of 115 major oral and maxillofacial surgeries were carried out during the period of this study. The most common procedures were enucleation of cysts (26.1%), dredging of odontogenic tumors or keratocysts (13.0%) and excision of benign lesions (12.2%). Wide excision of malignant lesions with or without neck dissection accounted for 10.4% while those resulting from trauma such as fracture fixations of the mandible and maxilla accounted for 11.3%. A smaller proportion of cases were performed for complex reconstructions, osteomyelitis or TMJ and salivary gland surgeries.Conclusion: Cystic and benign odontogenic pathologies comprised the majority of the major maxillofacial surgeries followed by trauma and procedures for malignancies. Continuous evaluation of surgical patterns helps in optimizing departmental resources, training and patient care strategies in tertiary settings.Update Dent. Coll. j: 2025; 15(2): 13-18